The Soybean Gene J Contributes to Salt Stress Tolerance by Up-Regulating Salt-Responsive Genes - Cheng, Qun; Gan, Zhuoran; Wang, Yanping; Lu, Sijia; Hou, Zhihong; Li, Haiyang; Xiang, Hongtao; Liu, Baohui; Kong, Fanjiang; Dong, Lidong (Frontiers in Plant Science, 2020)
Soybean [Glycine max (L.) Merr.] is an important crop for oil and protein resources worldwide, and its farming is impacted by increasing soil salinity levels. In Arabidopsis the gene EARLY FLOWERING 3 (ELF3), increased salt tolerance by suppressing salt stress response pathways. J is the ortholog of AtELF3 in soybean, and loss-of-function J-alleles greatly prolong soybean maturity and enhance grain yield. The exact role of J in abiotic stress response in soybean, however, remains unclear. In this study, we showed that J expression was induced by NaCl treatment and that the J protein was located in the nucleus. Compared to NIL-J, tolerance to NaCl was significantly lower in the NIL-j mutant. We also demonstrated that overexpression of J increased NaCl tolerance in transgenic soybean hairy roots. J positively regulated expression of downstream salt stress response genes, including GmWRKY12, GmWRKY27, GmWRKY54, GmNAC, and GmSIN1. Our study disclosed a mechanism in soybean for regulation of the salt stress response. Manipulation of these genes should facilitate improvements in salt tolerance in soybean